A systematic review of the integration of Industry 4.0 with quality-related operational excellence methodologies. Issue 1 (2nd January 2023) - Komkowski, Tim; Antony, Jiju; Garza-Reyes, Jose Arturo; Tortorella, Guilherme Luz; Pongboonchai-Empl, Tanawadee
Abstract: This study examines the common themes for integrating Industry 4.0 with quality-related operational excellence methodologies to provide a comprehensive overview of "what" and "how" to combine them in an initial integration process. In addition, the gaps in the present literature are aggregated, and a research plan for the future is proposed. The study is based on a systematic review of 37 papers published in academic journals between 2015 and 2021. Unlike previous reviews, this study concentrates on the "what" and "how" level of total quality management, Lean Six Sigma, and business process management as quality-related operational excellence methodologies integrated with Industry 4.0 to provide a practical perspective when executing their integration and implementation. Findings indicate a strong technical and data-driven integration focus across the three themes. Furthermore, modes of action as moderators of success were derived as initial variables to be included in quality-driven Industry 4.0 transitions. Identifying gaps in the present literature and defining a research agenda centered on operational principles opens up opportunities for future study with significant practical value.